Role of Paramagnetic Ions and Water Proton Spin-Lattice Relaxation Time in Biological Systems - Akber, S. F. (Nuklearmedizin - NuclearMedicine, 1993)
This paper summarizes the observations of different studies concerning the influence of paramagnetic ions on spin-lattice relaxation times in magnetic resonance imaging. Based on findings that manganese ion content in cancer tissues is decreased in comparison to normal tissues, the results of different papers analysing the influence of tissue manganese concentration on spin- lattice relaxation times are collected and compared. Neither the comparison between different organs, different animals nor the comparison between different tissues (normal and malignant) showed correlations of practical consequences between manganese concentrations and spin-lattice relaxation times. These results are consistent with those from studies with copper and iron ions in living systems.Die vorliegende Arbeit faßt als Literaturübersicht Beobachtungen über die Beeinflussung der T1-Relaxationszeit bei der Kernspintomographie durch paramagnetische Ionen zusammen. Ausgehend von Beobachtungen einer niedrigeren Mangankonzentration in karzinomatösen Geweben, verglichen mit normalen Geweben, werden die Ergebnisse verschiedener Studien zur Beeinflussung der T1-Relaxationszeiten durch Organ- und Tumor-Mangankonzentrationen zusammengestellt und verglichen. Weder im Vergleich verschiedener Organe, verschiedener Tierarten noch im Vergleich verschiedener Gewebe (normales und tumoröses Gewebe) fanden sich verwertbare Korrelationen zwischen Mangankonzentrationen und T1-Relaxationszeiten. Damit sind die Ergebnisse denen bei Kupfer- und Eisenionen in lebenden Geweben vergleichbar.
Keywords: Paramagnetic ions; manganese; spin-lattice relaxation time; magnetic resonance imaging